The mists of Avalon - Wolper, Mark M.; Eichinger, Bernd; Amir, Gideon; Scott, Gavin; Edel, Uli.; Huston, Anjelica; Margulies, Julianna, 1966-; Allen, Joan, 1956-; Mathis, Samantha; Goodall, Caroline, 1959-; Atterton, Edward; Vartan, Michael, 1968-; et al. ([United States] : Warner Home Video, 2001)
The mists of Avalon follows the women of Avalon from their childhoods through the ultimate fulfillment of their destinies in the battle between Christianity and Paganism that threatens to bring down Arthur's kingdom.
Originally produced as a television miniseries.
Based on the novel by Marion Zimmer Bradley.
Director of photography, Vilmos Zsigmond ; editors, Benjamin A. Weissman, Michael H. Friedlander ; music, Lee Holdridge ; costume designer, Carlo Poggioli ; production designer, Rodger Maus.
Anjelica Huston, Julianna Margulies, Joan Allen, Samantha Mathis, Caroline Goodall, Edward Atterton, Michael Vartan, Michael Byrne, Hans Matheson.
MPAA rating: Not rated.
Also issued on VHS.
Keywords: Arthur, -- King -- Drama; Britons -- Kings and rulers -- Drama; Avalon (Legendary place) -- Drama; Arthurian romances -- Adaptations; French language films; Feature films; Historical films; Fantasy films